Предмет: Алгебра,
автор: MaxPower
Упростите выражение (6- x)(2х+3) +х(2х -9).
В ответе получилось 18=0. А как правильно решить и записать ответ?
Ответы
Автор ответа:
0
(6- x)(2х+3) +х(2х -9)=12х+18-2х2-3х+2х2-9х=18
вот так!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
Автор ответа:
0
(6- x)(2х+3) +х(2х -9)=12х+18-2х²-3х+2х²-9х=12х+18-3х-9х=18
х=18
Похожие вопросы
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Литература,
автор: marichkamelnik380
Предмет: Немецкий язык,
автор: R1kkyF
Предмет: Физика,
автор: freake
Предмет: Химия,
автор: Tabea